Carte réduite, des costes de l'Acadie, de l'Isle Royale, et de la partie meridionale de l'Isle de Terre-Neuve - Chabert, Joseph Bernard, marquis de, 1724-1805 (Paris, France, 1753)
Hand coloured. Prime meridian Paris. Compass rose with rhumb lines. Depths shown by soundings. Bar scale in French and English marine leagues. Seal of sun king, upper left. Includes notes.